1995
DOI: 10.1111/j.1365-2273.1995.tb01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital epistaxis admission rate and ambient temperature

Abstract: The incidence of epistaxis admissions to hospital and their relationship to ambient temperature is examined. A retrospective analysis of 1211 patients with epistaxis sufficiently severe to warrant hospital admission was performed over a period of 1836 consecutive days. Daily average temperature data for this time-period were examined and compared with admission rates. A marked increase in hospital attendance was apparent during colder days. Patients were admitted at a rate of 0.829 patients per day for tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…For the purpose of eliminating the likely impacts of pollutants, the concentrations of SO 2 , NO 2 , and PM 10 were also included in the GAM model. Previous studies on the relationship between trauma and meteorological conditions generally employed a linear correlation analysis or developed regression equations [12,30,31]. To the best of our knowledge, it is the first time that the GAM model and the more advanced DLNM model are applied in this field.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of eliminating the likely impacts of pollutants, the concentrations of SO 2 , NO 2 , and PM 10 were also included in the GAM model. Previous studies on the relationship between trauma and meteorological conditions generally employed a linear correlation analysis or developed regression equations [12,30,31]. To the best of our knowledge, it is the first time that the GAM model and the more advanced DLNM model are applied in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental triggering factors have been described in the literature as explanations for hemorrhagic events. Principally, a marked increase in hospital attendance due to epistaxis during colder days has been described, 13 although Bray and colleagues, 14 with a larger series, found no correlation between temperature, seasonal preponderance, and epistaxis. Apart from epistaxis, association of bleeding occurence with meteorological variations was found.…”
Section: Discussionmentioning
confidence: 99%
“…Meteorological data for the period from January 2007 to December 2011 were obtained from the Catalan meteorological agency (http://www.meteo.cat, Accessed December 13,2012) for one weather station located in Badalona, 5 km away from our institution. Monthly mean values were obtained for maximum temperature, minimum temperature, mean temperature, atmospheric pressure, rainfall, relative humidity, and wind speed.…”
Section: Climatic Data Collectionmentioning
confidence: 99%
“…3 Tomkinson et al, showed that there was a marked increased in hospital attendence during colder days, where patients were admitted at a rate of 0.829 patients per day for temperatures less than 5 degree celsius (95% Confidence Interval: 0.737-0.928), compared with 0.645 patients per day between 5.1 and 10 degrees celsius, (95%.586-0.708). 13 Lewandowski et al, revealed that highest occurance of epistaxis was observed during the cold season between December and April (from 9.2 to 13.36% of all patients seen per month). 10 Our study showed that there is a good correlation between epistaxis and ambient temperature and average relation with the relative humidity.…”
Section: Discussionmentioning
confidence: 99%